Implementasi Kurikulum Merdeka dalam Pembelajaran Bahasa Arab di Kelas VII MTs Negeri 1 Kendal - Dina Lailatul Munasiroh (Walada: Journal of Primary Education, 2026)
This study aims to describe the implementation of the Kurikulum Merdeka (Merdeka Curriculum) in Arabic language learning at MTs Negeri 1 Kendal, along with its supporting and inhibiting factors. This research employs a qualitative descriptive method. Data were collected through observation, interviews, documentation, and literature review. The results indicate that: 1) The implementation of the Merdeka Curriculum in Arabic language instruction has been carried out in accordance with regulations, with an orientation toward language mastery as a global communication tool. 2) Key supporting factors include adequate learning facilities and the habituation of morning dhikr and prayer memorization, which accelerate students' linguistic adaptation. Meanwhile, the inhibiting factors identified are the students' low initial familiarity with the Arabic script and the limited allocation of lesson time compared to the number of students per class.